2013
DOI: 10.1371/journal.pone.0075324
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoxia in ALS Is Related to Cognitive Dysfunction and Can Occur as Clusters of Desaturations

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that leads to progressive weakness of the respiratory and limb muscles. Consequently, most patients with ALS exhibit progressive hypoventilation, which worsens during sleep. The aim of this study was to evaluate the relationship between nocturnal hypoxia and cognitive dysfunction and to assess the pattern of nocturnal hypoxia in patients with ALS.MethodTwenty-five patients with definite or probable ALS underwent neuropsychologic testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Mutant SOD1 mice which experienced chronic intermittent hypoxia showed reduced performance on the rotarod, reduced ability in the wire hanging test, poorer spatial memory as assessed by the Y-maze, and a greater loss of motor neurones, compared to the SOD1 G93A mice under normoxia conditions [81]. This correlates with data recorded from ALS patients, which compared nocturnal hypoxia with cognitive dysfunction [82]. The results demonstrated that patients who experience nocturnal hypoxia (as defined as the average O2 saturation being <95% for more than 10% of the sleep time) showed a significant decrease in their memory retention and retrieval efficiency abilities.…”
Section: Hypoxia and The Response To Stresssupporting
confidence: 75%
“…Mutant SOD1 mice which experienced chronic intermittent hypoxia showed reduced performance on the rotarod, reduced ability in the wire hanging test, poorer spatial memory as assessed by the Y-maze, and a greater loss of motor neurones, compared to the SOD1 G93A mice under normoxia conditions [81]. This correlates with data recorded from ALS patients, which compared nocturnal hypoxia with cognitive dysfunction [82]. The results demonstrated that patients who experience nocturnal hypoxia (as defined as the average O2 saturation being <95% for more than 10% of the sleep time) showed a significant decrease in their memory retention and retrieval efficiency abilities.…”
Section: Hypoxia and The Response To Stresssupporting
confidence: 75%
“…The pyramidal cells of Sommer's sector in the hippocampus and of layers 3 and 5 in the neocortex, and the Purkinje cells in the cerebellum are cell populations in the adult central nervous system particularly vulnerable to hypoxic injury . Park et al identified a significant correlation of the duration of nocturnal hypoxia with impaired memory retention and retrieval efficiency in ALS patients . These additional cognitive deficits likely further compromise the precious remaining quality of life for patients with ALS.…”
Section: Consequences Of Nocturnal Hypoventilationmentioning
confidence: 99%
“…37 Park et al identified a significant correlation of the duration of nocturnal hypoxia with impaired memory retention and retrieval efficiency in ALS patients. 38 These additional cognitive deficits likely further compromise the precious remaining quality of life for patients with ALS.…”
Section: Consequences Of Nocturnal Hypoventilationmentioning
confidence: 99%
“…A researcher found that cognitive decline was more severe and frequent in Hodgkin lymphoma patients compared to the healthy population [48]. Based on recent study patients with "nocturnal hypoxia" had poor memory retention compared with healthy individuals [49]. Indeed, "oximetry" (Fig.…”
Section: Quantitative Analysismentioning
confidence: 99%